Sistem Informasi Geografis (SIG) Pemetaan Kost-Kosan Menggunakan Metode Formula Haversine - Sa’ad, Muhammad Ibnu; Surahmanto, Muhammad; Soemari, Muhammad Rizki Pratono; K, Kusrini; Mustafa, M. Syukri (STIKOM Tunas Bangsa Pematangsiantar, 2020)
Geographic Information System ia a geospatial software system that has the ability to build, store, manage and display geo-referenced information, for example data that is identified by location. By using GIS, it is expected that it will be easier for prospective students and students to find out the location of boarding houses that are located around the campus of Mulawarman University. The system development method uses the waterfall method. While the system design method uses UML (Unified Modelling Language) to visualize, determine, develop and document a software system. The algorithm used in this study uses the haversine formula which will later help to find the nearest boarding house location around the campus of Mulawarman University, the haversine formula will produce the shortest distance between two points, for example on a ball taken from the longitude and latitude. The result of this study will disply detailed boarding location information, besides that on this geograpihic information system the user will later be able to see the details of boarding and admin data can change, add data to the boarding owner and be technically responsible for the running of the application, while the boarding owner is only responsible on managing boarding data on their respective users.